2021
DOI: 10.1080/21655979.2021.1946305
|View full text |Cite
|
Sign up to set email alerts
|

m6A RNA methylation regulators were associated with the malignancy and prognosis of ovarian cancer

Abstract: N6-methyladenosine (m6A) RNA methylation regulators play a regulatory role in tumor pathogenesis and development. However, the role of m6A regulator genes in ovarian cancer (OC) has not been fully elucidated. This study aims to investigate the mRNA expressions, clinicopathological features, and prognostic values of m6A regulators in OC. Here, we demonstrate that the 17 m6A RNA methylation regulators are differentially expressed in ovarian cancer and normal tissues. By using consensus clustering, all ovarian ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 96 publications
0
23
0
Order By: Relevance
“…For example, KIAA1429-induced m 6 A promoted the translation of c-MYC, BCL2, and Phosphatase and tensin homolog (PTEN) mRNAs in the human acute myelocytic leukemia (AML) cells, suppressing the differentiation and apoptosis of AML cells [ 8 ]. In OC, KIAA1429 and METTL3 is associated with the prognosis of OC patients [ 9 , 10 ]. METTL3 promotes OC growth and invasion through the regulation of AXL receptor tyrosine kinase (AXL) translation and epithelial to mesenchymal transition (EMT) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, KIAA1429-induced m 6 A promoted the translation of c-MYC, BCL2, and Phosphatase and tensin homolog (PTEN) mRNAs in the human acute myelocytic leukemia (AML) cells, suppressing the differentiation and apoptosis of AML cells [ 8 ]. In OC, KIAA1429 and METTL3 is associated with the prognosis of OC patients [ 9 , 10 ]. METTL3 promotes OC growth and invasion through the regulation of AXL receptor tyrosine kinase (AXL) translation and epithelial to mesenchymal transition (EMT) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…IGF2BP3, KIAA1429, IGF2BP1, YTHDF3, ZC3H13, YTHDC1, and METTL14 can be used as prognostic markers of endometrial cancer (93,94). HNRNPA2B1, KIAA1429, and WTAP can be used as prognostic markers of ovarian cancer (114). However, these studies are based only on systematic analyses of public databases.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics and Cox multivariate analysis showed the significant correlation between high expression of WTAP and ovarian cancer prognosis(113). Meanwhile, analysis of other gene sets found that the prognosis of ovarian cancer was associated with HNRNPA2B1, KIAA1429, and WTAP(114). Na et al identified NEBL, PDGFRA, WDR91, and ZBTB4 genes as potential independent prognostic risk characteristics of ovarian cancer(115).…”
mentioning
confidence: 99%
“…The methyltransferase catalyzes the production of m6A in the form of complexes in the nucleus. The complex consists of an interacting protein, such as METTL14 and WTAP [ 36 ]. These proteins modulate m6A modification in non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%